2017
DOI: 10.1093/molbev/msx114
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the Mutation Underlying Fleece Variation and Discriminating Ancestral Hairy Species from Modern Woolly Sheep

Abstract: The composition and structure of fleece variation observed in mammals is a consequence of a strong selective pressure for fiber production after domestication. In sheep, fleece variation discriminates ancestral species carrying a long and hairy fleece from modern domestic sheep (Ovis aries) owning a short and woolly fleece. Here, we report that the “woolly” allele results from the insertion of an antisense EIF2S2 retrogene (called asEIF2S2) into the 3′ UTR of the IRF2BP2 gene leading to an abnormal IRF2BP2 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 25 publications
3
56
1
1
Order By: Relevance
“…A few studies have found that genetic polymorphisms in candidate genes can account for various hair traits in different species (Adhikari et al, 2016;Demars et al, 2017;Morgenthaler et al, 2017). Some critical signaling pathways, including the wingless-related integration site (WNT), ectodysplasin A receptor (EDAR), and bone morphogenetic proteins (BMP) pathways, are regarded as regulatory hubs during fiber development (Lu et al, 2016;Telerman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have found that genetic polymorphisms in candidate genes can account for various hair traits in different species (Adhikari et al, 2016;Demars et al, 2017;Morgenthaler et al, 2017). Some critical signaling pathways, including the wingless-related integration site (WNT), ectodysplasin A receptor (EDAR), and bone morphogenetic proteins (BMP) pathways, are regarded as regulatory hubs during fiber development (Lu et al, 2016;Telerman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Searches for genome intervals, genes and polymorphisms which determine performance for economically important traits in sheep have resulted in revealing signatures of selection likely associated with coat colour [5][6][7], tail fat deposition [8], muscle growth [9], milk yield [10], reproductive traits [6,11], wool [12], resistance to parasites [13], presence/absence of horns [6,11], etc. These chromosome regions contain markers (genes or regulatory sequences) which should be the focus of future efforts on the improvement of local and multinational breeds using the rapidly-developing plethora of contemporary genetics tools.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of retrogenes in the canine reference genome reported ~70 functional retrogenes in the dog; however, only the previous CFA18 FGF4 retrogene insertion has been reported to be associated with a disease causing phenotype 26,45 . Similarly in humans, the formation of processed pseudogenes in general, as well as those that retain their intended function and cause disease, is rare [46][47][48][49][50][51] .…”
Section: Discussionmentioning
confidence: 99%